Critical thinking and creativity in an eighth-grade music classroom: a comprehensive composition - Martens, Jeffrey (Kansas State University, 2021)
In my experience, the creative aspect of music has been ignored too often in public school music programs. The multi-part lesson I have designed will incorporate as many aspects of the music process as possible, especially creativity. It can be used with virtually any age, skill level, or primary instrument, depending on need. My focus here is with 8th grade students who have a basic foundation of musical skills. Students will use all their prior musical skills and knowledge to compose a complete melody. They will notate their melody using a music notation program they have easy access to, such as Noteflight, MuseScore, or Quaver. The teacher will have provided prior training on how to use the basic functions of the chosen program. Students will work at their own pace and produce a high-quality product. At this point, some brief training about harmony and accompaniment will be provided by the teacher. Then, a key specific “cheat sheet” that contains common chords, common chord progressions, and simple, repeatable accompaniment patterns will be provided for students to use if they please. Students will write an accompaniment to go with their melody. This accompaniment can be as simple as root position chords placed in sensible locations, or as complex as the student’s ability will allow. The goal is creativity and quality work. The composer will sing or play their melody for the class using any instrument he or she is comfortable with, while the computer plays the student created accompaniment. If nerves are too much of an issue, the computer can play both the melody and accompaniment for the student. The composer will then talk the class through his or her creative process as well as any history behind the song. At this point, other students will have the opportunity to discuss what they noticed and appreciated about the piece. If the composer wishes, the class can provide constructive comments that could make the piece stronger. Composers will then have the opportunity to revise, make additions, alterations, or orchestrate the piece, with the possibility of a school ensemble performing it for an audience. Alternatively, the composer could choose to simply move on to a completely new project. Throughout the entire process, the teacher, the internet, books and other resources will be available for student composers to use at their convenience. At this point in my journey through a master’s degree, I have noticed several career changing developments in my approach to teaching music. The most surprising and valuable of which is that I have gained a better understanding of what I believe about music education, its place in public schools, and why it is important. The direction of music education is changing, at least in part, to become more student-centered; with individual interest, knowledge, skill, and context growing in importance. I, as a music educator, must continue to learn, adapt, and change over time to make music education relevant and meaningful to ALL students. I have noticed other powerful and complex skills have developed, as well. I have grown in my ability to learn on my own; gather, organize, and present information on a given topic, in a variety of ways. I can effectively find, understand, and use research in my quest to learn and grow. The complex skill of classroom management is something I have been intently focusing on since my research class, in the summer of 2019. I have been observing, reading, writing, contemplating, and practicing this skill. Other salient skills that have expanded include choosing appropriate music, score study and preparation, and the skill and confidence to arrange music for any purpose I may encounter as a music educator.
Keywords: Creativity; Lesson plan; Music; Middle school; Composition; Education